2015
DOI: 10.1371/journal.pone.0114811
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Foot-And-Mouth Disease Viruses (FMDVs) from Ugandan Cattle Outbreaks during 2012-2013: Evidence for Circulation of Multiple Serotypes

Abstract: To investigate the foot-and-mouth disease virus (FMDV) serotypes circulating in Uganda’s cattle population, both serological and virological analyses of samples from outbreaks that occurred during 2012–2013 were performed. Altogether, 79 sera and 60 oropharyngeal fluid (OP)/tissue/oral swab samples were collected from herds with reported FMD outbreaks in seven different Ugandan districts. Overall, 61/79 (77%) of the cattle sera were positive for antibodies against FMDV by PrioCHECK FMDV NS ELISA and solid phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
46
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 49 publications
10
46
0
Order By: Relevance
“…Further studies may be warranted to also include serotypes C and SAT 3, although serotype C has not been detected in any country since 2004. SAT 3‐specific antibodies have been recorded in sera from west and central Africa (Ehizibolo et al., ; Ludi et al., ) and from eastern Africa (Ayebazibwe et al., ; Dhikusooka et al., ; Mwiine et al., ; Namatovu et al., ), although this serotype has not previously been detected in Niger. Although the sampling strategy is different to that implemented by Ludi et al.…”
Section: Discussionsupporting
confidence: 54%
“…Further studies may be warranted to also include serotypes C and SAT 3, although serotype C has not been detected in any country since 2004. SAT 3‐specific antibodies have been recorded in sera from west and central Africa (Ehizibolo et al., ; Ludi et al., ) and from eastern Africa (Ayebazibwe et al., ; Dhikusooka et al., ; Mwiine et al., ; Namatovu et al., ), although this serotype has not previously been detected in Niger. Although the sampling strategy is different to that implemented by Ludi et al.…”
Section: Discussionsupporting
confidence: 54%
“…Reports from the Ugandan Ministry of Agriculture, Animal Industry and Fisheries (MAAIF) indicate that there was an increase in the number of FMD outbreaks between 2000 and 2007 as compared to the 1990s (Kasambula et al, ). Recent studies conducted in the country have shown the circulation of at least four serotypes including: O (topotype: EA‐2; strains: U24/11, and U07/11), A (topotype:G‐I; strain: U74/13), SAT 1 (topotype: IV; strain: UGA‐116‐13/2011) and SAT 2 (topotype: IV; strain: U73/13) (Ayebazibwe, Mwiine, Tjørnehøj, et al, ; Balinda, Belsham, et al, ; Dhikusooka et al, ; Mwiine et al, ; Namatovu, Tjørnehøj, et al, ). In addition, serotype SAT 3 virus was isolated from a healthy calf in Uganda though this serotype does not appear to be widely distributed (Dhikusooka et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, vaccines may not provide adequate protection against regionally circulating FMD viruses. For many years, FMD caused by serotype A has been a rare occurrence in Uganda, only observed in Soroti district in 2002 (Muleme et al, ) and in Wakiso district in 2013 (Namatovu, Tjørnehøj, et al, ). As such, imported FMD vaccines in Uganda have historically not contained FMD serotype A.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of multiple FMDVs in the same geotemporal space hinders disease control and may pose an increased risk of emergence of new strains. Numerous studies have reported serological evidence of infection with multiple serotypes within the same animal, which indicates evidence of cumulative, lifetime exposure (Eldaghayes et al., ; Ludi et al., ; Namatovu et al., ; Sikombe et al., ; Wungak et al., ). However, simultaneous coinfection is a distinct subcategory of multiple exposures and has been reported rarely in clinical samples from cattle (Jamal, Ferrari, Ahmed, Normann, & Belsham, ; Souley Kouato et al., ; Ullah et al., ; Wungak et al., ), but is believed to occur more frequently in oropharyngeal fluid samples from African Cape buffalo (Anderson, Doughty, Anderson, & Paling, ; Hedger, ; Vosloo et al., ).…”
Section: Introductionmentioning
confidence: 99%